Kualitas Pelayanan Perizinan Pada Kantor Pelayanan Perizinan Terpadu (Kppt) Kota Surakarta Provinsi Jawa Tengah - -, Suwardi - (Transformasi, 2012)
AbstractPermit service is strategic function of governance execution, development and social. Thisresearch measure the permit service with the approach of service quality ( SERQUAL). Researchorient the customer perception to accepted permit service. Analytic research observasional withthe transversal cross sectional this analyse 60 data of perception cutomer as responder to permitservice which he is accepted from Inwrought Permit KPPT) Kota Surakarta. Result of Surveydiscription quality of service of permit of good KPPT Kota Surakarta tend to toward very good attotalizeing dimension consisted by the reliabilitas, responsivenness, assurance, empathy, andtangible.Keyword: Customer; Service; Perseption and Quality